A game for swallows : to die, to leave, to return - Abirached, Zeina, 1981- (Graphic Universe, 2012)
Living in the midst of civil war in Beirut, Lebanon, Zeina and her brother face an evening of apprehension when their parents do not return from a visit to the other side of the city.